ANALISIS PENGENDALIAN KUALITAS PRODUK KNOB 30VYG508-206^V DENGAN METODE SEVEN TOOLS DI PT. XYZ - Indra Gumelar; Rizki Fitria Annisa; Agung Widarman; Iman Thoriq (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2024)
The current industrial development makes companies compete to maintain and improve the quality of their products. This research is aimed at identifying the causes of defects, as well as reducing defective products and providing alternative repair proposals. This study uses the help of the seven tools method to analyze data. The data used for research needs is a production report that contains information on the number of products and the number of defective products in the period July 2023 – June 2024. The results obtained in this study are known to have three types of defects in Knob 30VYG508-206^V products, namely Spots, Bubbles, and Burries. From the results of the Pareto diagram, it can be seen that Bubrry's defect is the most dominant type of defect with 34%. Some of the factors that cause defects based on fishbone diagrams are human, machine, and method factors. The proposals given in this study are the procurement of training for employees, to the formulation of SOPs that regulate the manufacturing process and standards for the production of Knob 30VYG508-206^V products in detail.